The Influence of Emotional Intelligence and Peer Support on Learning Motivation among Students of the PPKn Study Program, Faculty of Teacher Training and Education, Universitas Riau - Noviana, Risa; Supentri, Supentri; Radini, Radini (Universitas Muhammadiyah Enrekang, 2026)
This study was motivated by the importance of learning motivation as a key determinant of students’ academic success, which is influenced not only by cognitive abilities but also by emotional factors and the social environment. In practice, differences are still observed in students’ ability to manage emotions, their level of self-awareness regarding personal feelings, and the quality of support received from peers. These differences appear to affect students’ enthusiasm, consistency, and resilience in facing academic challenges. This study employed a quantitative research design with a correlational approach. The population consisted of all active students enrolled in the odd semester of the Civic Education (PPKn) Study Program, Faculty of Teacher Training and Education, Universitas Riau, in the 2025/2026 academic year. A probability sampling technique, specifically simple random sampling, was used to select 182 students as research participants. Data were collected using questionnaires, and data analysis was conducted with the assistance of SPSS software. The results indicate that: (1) emotional intelligence has a positive and significant effect on learning motivation, with a significance value of 0.000 and a t-value of 5.991; (2) peer support has a significant effect on learning motivation, with a significance value of 0.000 and a t-value of 3.550; and (3) emotional intelligence and peer support simultaneously have a significant effect on learning motivation, as evidenced by the simultaneous test (F-test) results showing a significance value of 0.000 < 0.05 and an F-value of 55.826 > 3.05. Therefore, it can be concluded that students’ learning motivation is influenced by emotional intelligence and peer support.